Evidence for a fruit fly hemangioblast and similarities between lymph-gland hematopoiesis in fruit fly and mammal aorta-gonadal-mesonephros mesoderm. - Mandal, L.; Banerjee, U.; Hartenstein, V. (Nature Genetics, 2004)
The Drosophila melanogaster lymph gland is a hematopoietic organ and, together with prospective vascular cells (cardioblasts) and excretory cells (pericardial nephrocytes), arises from the cardiogenic mesoderm. Clonal analysis provided evidence for a hemangioblast that can give rise to two daughter cells: one that differentiates into heart or aorta and another that differentiates into blood. In addition, the GATA factor gene pannier (pnr) and the homeobox gene tinman (tin), which are controlled by the convergence of Decapentaplegic (Dpp), fibroblast growth factor (FGF), Wingless (Wg) and Notch signaling, are required for the development of all cardiogenic mesoderm, including the lymph gland. Here we show that an essential genetic switch that differentiates between the blood or nephrocyte and vascular lineages involves the Notch pathway. Further specification occurs through specific expression of the GATA factor Serpent (Srp) in the lymph-gland primordium. Our findings suggest that there is a close parallel between the molecular mechanisms functioning in the D. melanogaster cardiogenic mesoderm and those functioning in the mammalian aorta-gonadal-mesonephros mesoderm.